Geopolitics of Natural Gas Supply in Europe – Poland between the EU and Russia - Szul, Roman (European Spatial Research and Policy, 2011)
The article analyses possible interests, attitudes and activities of the major actors in the ‘natural gas supply game’ in Europe after 1990: Russia/Gazprom, alternative suppliers like countries in the Caspian Sea area, the main consumers of gas and transit countries. It stresses that behaviour of the actors depends on the changing international political and economic situation and conditions in individual countries. Special attention is paid to pipeline projects: Nord Stream, South Stream and Nabucco, and reactions to them, such as building a LGN terminal at Świnoujście (Poland), North-South (Baltic-Adriatic) energy corridor and the Polish-Russian gas contract of 2010.